Overlapping activation pattern of bitter taste receptors affect sensory adaptation and food perception - Lang, Roman; Lang, Tatjana; Dunkel, Andreas; Ziegler, Florian; Behrens, Maik (Frontiers in Nutrition, 2022)
The composition of menus and the sequence of foodstuffs consumed during a meal underlies elaborate rules. However, the molecular foundations for the observed taste- and pleasure-raising effects of complex menus are obscure. The molecular identification and characterization of taste receptors can help to gain insight into the complex interrelationships of food items and beverages during meals. In our study, we quantified important bitter compounds in chicory and chicory-based surrogate coffee and used them to identify responsive bitter taste receptors. The two receptors, TAS2R43 and TAS2R46, are exquisitely sensitive to lactucin, lactucopicrin, and 11β,13-dihydrolactucin. Sensory testing demonstrated a profound influence of the sequence of consumption of chicory, surrogate coffee, and roasted coffee on the perceived bitterness by human volunteers. These findings pave the way for a molecular understanding of some of the mixture effects underlying empirical meal compositions.